Sebaran Bellucia pentamera Naudin Di Kawasan Objek Wisata Kapalo Banda Taram Kabupaten Lima Puluh Kota - Solfiyeni Solfiyeni; Siska Yuningsih (Universitas Andalas, 2023)
Kapalo Banda Taram Tourism Area, Lima Puluh Kota Regency is one of the tropical rain forest areas in West Sumatra which has a high level of biodiversity that can be disturbed due to the presence of invasive plants, one of which is Bellucia pentamera. The purpose of this study was to determine the distribution of B. pentamera, to determine the effect of the number of Bellucian on the number of non-Bellucian and to determine the effect of distance from the river and light intensity on the distribution of B. pentamera. The research using the belt transect with a plot size of 20x50 m2. Data analysis using the Morisita Index and Simple Linear Regression formulas. The distribution of B. pentamera was quite large with the distribution pattern of B. pentamera sapling strata is clustered, while the tree strata had a uniform distribution pattern. The number of Bellucian individuals affects the presence of non-Bellucian individuals as indicated by a negative effect on species diversity, a decrease in the number of species, high dominance and habitat colonization which will limit resources and space for the growth of other species. The distance from the river affects the distribution of B. pentamera where the closer the distance from the river tends to increase the presence of B. pentamera, while the light intensity does not affect the presence of B. pentamera.